O bibliotecário no Exército Brasileiro: satisfação e motivação para o trabalho militar do profissional da informação - Oliveira, Júlio Cesar Pinto de (2020)
This Dissertation presents and contextualizes the themes "Motivation" and "Job Satisfaction", correlating the Librarian with the Army. Its general objective is to identify which are the most motivating factors and their relationship with satisfaction for the military work of the librarian in the Brazilian Army, observing the differences between the stabilized and the temporary. It explains, in general lines, the “Brazilian Army”, presenting a brief history, its constitutional mission, the characteristics of the military and the career plan, giving greater emphasis to the professionals who have stability, provided by the approval in public competition, and to those who they have a temporary work contract of a maximum of eight years, due to the simplified selection process they carried out. He explains that the librarian became part of the Army's stable career in 2012, currently counting on nine professionals. It also indicates that there are twenty-six temporary librarians. It presents the Army Integrated Library Network (BIE Network) and its importance for the Army Librarian. It presents details of the librarian profession, such as characteristics of the bachelor in Librarianship and the elements that are guided by the International Federation Library Association (IFLA) to compose the curricula of undergraduate courses, in addition to highlighting the professional's skills. After conducting a Systematic Bibliographic Review (RBS) in scientific databases, studies were identified that relate “motivation and military service” and “motivation and librarian work”. Motivational theories were explained, with greater emphasis, the Two Factor Theory, by Frederick Herzberg, from 1959. Through a questionnaire built from previous studies that used this Theory as a theoretical framework, collected perceptions about work, routine and motivations for working in the military as a librarian, highlighting the factors that produce the greatest satisfaction. The collected data were analyzed using descriptive statistics; hierarchical groupings (cluster); Mann-Whitney non-parametric test; and Spearman correlation. The survey results indicate that there is little variation in motivation and satisfaction with military work between stabilized and temporary librarians, except for two variables (one linked to the relationship with peers and one linked to the job itself). In both variables there was a significant difference (at the level of 5%) in motivation between the groups, showing that stabilized librarians have higher levels of motivation for military work than temporary librarians. Finally, it highlights that the profile of the military librarian is predominantly female, between thirty and thirty-nine years old, who concluded, at least, a specialization course lato sensu, who identifies strictly military activities as demotivating and who perceives professional recognition, remuneration and relationships with subordinates, the most valuable motivational factors for obtaining satisfaction in military work.